Law incentives for juvenile recruiting by drug trafficking gangs: empirical evidence from Rio de Janeiro - Montolio, Daniel (2020)
We evaluate the deterrence effects of the age of criminal responsibility on total drug trafficking and homicide crimes per age, based on a quasi-experiment generated by differences in punishment severity for these crimes prescribed by the Statute of the Child and Adolescent and by the Penal Code in Brazil. To this end, information from arrests conducted by the civil and military police of the state of Rio de Janeiro in 2016 and 2017 is used to estimate the local effects of treatment through a Regression Discontinuity Design. Instead of using recidivism data and/or grouping crimes with distinct punishment severity, we use as outcome variable the total number of arrests (crimes) per age for drug trafficking and homicides, which are the most common crimes related to organized crime in Rio de Janeiro. (...